RETRACTED: Formation of competitiveness of agricultural enterprises of the Kyrgyz Republic - Parpieva Nurzhamal; Matikeeva Nazgul; Sulaimanova Ainura; Belek uulu Esenbek; Oganova Gulnara (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001